Carlyle's European politics - Middleton, A (Saint Joseph’s University Press, 2023)
This article attempts a general assessment of Carlyle’s attitudes towards the politics of contemporary Europe. It asks where the Continent fitted in his political thought after 1830, and how he stood relative to the great European questions of his maturity. It emphasises the ambition with which Carlyle’s published political and social writings swept around Europe, and the confidence with which they claimed to offer authoritative diagnoses of Europe’s ills. But the article also argues that Carlyle’s engagement with Continental politics was largely superficial. He was never a committed student of the subject, and confined his attention to headline developments and broad political strokes. Like so many of his contemporaries, he was invigorated by the spectacle of the revolutions of 1848, but he did not end up sharing the more serious interest in contemporary European affairs which infected so much of British political culture in the 1850s and 1860s. His attitudes towards specific Continental nations and statesmen, which for the most part he did not place before the public, aligned relatively closely with the general principles about politics and leadership he outlined in other contexts.